Studies on Phenoloxidase Activity and its Sensitivity to Metabisulphite in Frozen Metapenaeus Monoceros - R., Chakrabarti; S.S., Gupta (Fishery Technology, 2025)
The incidence of black spot in frozen prawns was observed in many cases during thawing at tropical ambient temperatures. A dip in 0.5% (100% purity basis) sodium metabisulphite solution for 30 seconds controlled black spot in frozen Metapenaeus monoceros upto 10 months. Phenoloxidase activity in the shell extract of prawn showed a decreasing trend during frozen storage (-180C). The activity was lower in the sulphite treated sample when compared with the untreated sample. Residual sulphur dioxide in thawed meat was within permitted limits.